Mereduksi Kecemasan Siswa Melalui Konseling Cognitive Behavioral - I Putu Agus Apriliana; Kadek Suranata; I Ketut Dharsana (Indonesian Journal of Educational Counseling, 2019)
REDUCING STUDENTS’ ANXIETY THROUGH COGNITIVE BEHAVIORAL COUNSELING. Anxiety experienced by students at school can later affect their academic success at school. For this reason, this study tries to describe students' anxiety and efforts to reduce them through cognitive behavioral counseling. Anxiety in students can be interpreted as a condition that is full of worries and fears, feeling depressed, not calm, feeling guilty, feeling insecure and chaotic-minded accompanied by physical tension to certain situations. The characteristics of students who experience anxiety are divided into three parts, namely physical, behavioral and cognitive. The steps to reduce student anxiety through cognitive behavioral counseling are 1) identifying and knowing the level of student anxiety, 2) carrying out cognitive behavioral counseling, namely: initiating counseling, discussing content in the session, checking the events of the previous week, Core counseling , assigning tasks for the next meeting, and evaluating the session. Then, 3) Follow up. This article is expected to contribute as a scientific literature in the field of guidance and counseling, especially for school counselor in dealing with student anxiety through counseling services using a cognitive behavioral approach at school.